Morphological changes of the gall bladder in patients with chronic calculous colecystitis on the background of type 2 diabetes - Pyuryk , M.V. (Морфологія / Morphologia / Morfologìâ, 2022)
Background. Cholelithiasis occurs in approximately 15% of the adult population. The number of patients at housing and communal services grows every year and increases by 1.5–2 times every decade. Today, chronic calculous cholecystitis (CCC) is one of the most common diseases of the abdominal cavity. Objective: to improve the results of treatment by studying the pathohistological features of the gallbladder wall in patients with chronic calculous cholecystitis with accompanying diabetes. Methods. An analysis of the treatment of patients in the Department of Minimally Invasive Surgery of the Ivano-Frankivsk Regional Hospital was carried out. In order to study the specified features, a morphological study of the gallbladders of 73 patients with chronic calculous cholecystitis (group I) and 69 patients with chronic calculous cholecystitis with accompanying diabetes mellitus type II (group II) was conducted. Results. It was established that total damage to the entire organ was found in patients with CCC with accompanying diabetes significantly more often (in 33.3% of patients) than in patients with CCC (in 13.7%). During the examination of the gallbladder in patients of the II group, manifestations of the inflammatory process, pronounced sclerosis, infiltration of the mucous membrane by xanthoma cells, a decrease in the secretory activity of the epithelium of the mucous membrane, and a tendency to decrease in the size of the gallbladder due to sclerosing were observed in patients of this group. An increase in the thickness of the gallbladder wall due to hyperplasia of the mucous membrane and hypertrophy of the muscular membrane was characteristic for patients of the 1st group. In the patients of the II group studied by us, multiple concretions occurred more often, compared to the data of the patients of the I group. Conclusion. 1. Chronic calculous cholecystitis without concomitant pathology was 1.8 times more common in women, and in the case of concomitant diabetes mellitus, no significant difference between indicators in men and women was found (p>0.05). 2. The average age of patients operated on for chronic calculous cholecystitis with accompanying diabetes was lower compared to the indicators of the first group of patients (54.7+15.4 years vs. 61.2+13.2 years). 3. In patients with CCC with concomitant diabetes mellitus, multiple calculi were detected in the lumen of the gastrointestinal tract 13.9% more often, and chronic hypoplastic cholecystitis was diagnosed 57.5% more often. 4. In the wall of the gastrointestinal tract of patients with diabetes mellitus and CCC, a pathohistological examination revealed the phenomena of sharply expressed sclerosing of the mucous and muscle membranes, lipid infiltration with the formation of xanthoma cells and a decrease in the secretory activity of the epithelium of the folds of the mucous membrane.